An anode sheet preparation method based on electrolyte moisture management and a battery

CN122659043APending Publication Date: 2026-08-28ZHEJIANG LANYA NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610896391.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-22
Publication Date
2026-08-28

AI Technical Summary

Technical Problem

1.水分管控维度单一,风险识别严重不足:行业内通常仅对固态电解质浆料的整体水分进行管控,完全忽略了纳米颗粒表面吸附水的独立影响,导致大量"浆料水分合格但极片水分超标"的隐性风险

Benefits of technology

1.建立了行业首个三维水分管控体系

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122659043A_ABST
    Figure CN122659043A_ABST
Patent Text Reader

Abstract

The application provides a positive plate preparation method based on electrolyte moisture control and a battery. The core rule that "moisture of solid-state electrolyte wet powder is a key factor affecting the moisture of the positive plate" is first determined, and the long-standing error cognition in the industry that "controlling the total moisture of the slurry is enough" is corrected, providing a scientific theoretical basis for moisture control. By detecting three indexes before the slurry is used, the moisture of the positive plate can be accurately predicted whether it will exceed the standard, and the risk of scrapping the whole batch of positive plates is fundamentally avoided. By strictly controlling the moisture of the positive plate, the side reactions in the battery are effectively reduced, the capacity retention rate, rate performance and cycle life of the battery are improved, and the safety hazards such as swelling and thermal runaway caused by excessive moisture are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new energy battery technology, and in particular to a method for preparing a positive electrode based on electrolyte moisture control and a lithium-ion battery. Background Technology

[0002] Lithium-ion batteries, as core components of new energy storage, are widely used in new energy vehicles, consumer electronics, and energy storage. However, their cathodes still face problems such as structural distortion during charging and discharging, frequent interfacial side reactions, high ion transport impedance, and insufficient thermal safety, which restrict the synergistic improvement of battery energy density, cycle life, and adaptability to extreme environments. Incorporating solid electrolyte particles into the cathode can effectively improve the electrical and safety performance of the cell. Nanoscale solid electrolyte powders, due to their small particle size, large specific surface area, and high specific surface energy, are prone to agglomeration when directly added to electrode slurry. Therefore, they are often added to the cathode slurry in the form of solid electrolyte slurry to obtain a uniformly dispersed cathode sheet.

[0003] The addition of new components to the positive electrode will introduce additional moisture. Excessive moisture will directly affect the homogenization process of the positive electrode slurry, increase side reactions, and lead to problems such as capacity decay, decreased rate performance, shortened cycle life, and even seriously affect the safety performance of the cell. Nanoscale solid electrolyte particles, due to their large specific surface area and hydrophilic groups, readily adsorb moisture. Therefore, moisture in solid electrolytes exists in two forms: on the surface of the solid electrolyte particles and in the solvent. Figure 1 As shown.

[0004] When solid electrolyte slurry is added to the positive electrode homogenate, after the electrode coating and baking are completed, the solvent moisture introduced by the solid electrolyte slurry will evaporate with the drying of the electrode. However, due to the low baking temperature of the electrode, the adsorbed water on the surface of the solid electrolyte particles is difficult to completely remove, which leads to the risk of high or even excessive moisture content in the electrode.

[0005] The existing technology has the following core defects: 1. Limited scope of moisture control and serious lack of risk identification: The industry usually only controls the overall moisture of solid electrolyte slurry, completely ignoring the independent influence of water adsorbed on the surface of nanoparticles, resulting in a large number of hidden risks of "slurry moisture is qualified but electrode moisture exceeds the standard".

[0006] 2. Misconception about key correlations: Experiments have shown that the moisture content of the electrode sheet is not strongly correlated with the overall moisture content of the solid electrolyte slurry. On the contrary, the moisture content of the wet powder of the solid electrolyte sheet is strongly positively correlated with the moisture content of the electrode sheet. Current technology has failed to discover this essential law.

[0007] 3. Lack of dedicated testing methods: There is currently no industry-standardized testing method for the moisture content of wet powder solid electrolyte slurry, making it impossible to accurately quantify the adsorbed water content on the surface of nanoparticles.

[0008] 4. Post-production testing mode, resulting in huge economic losses: Current technology usually conducts moisture testing only after the electrode is prepared. If the moisture content exceeds the standard, the entire batch of electrode has to be scrapped, resulting in multiple wastes of raw materials, energy and manpower. Summary of the Invention

[0009] To address the technical problems existing in the prior art, the present invention provides the following technical solution: On the one hand, a method for preparing a positive electrode based on electrolyte moisture control is provided, including the following steps: S1: Three independent moisture tests were performed on the non-aqueous solid electrolyte slurry: total moisture content of the slurry, moisture content of the supernatant after centrifugation, and moisture content of the lower wet powder after centrifugation. S2: Determine whether the solid electrolyte slurry is qualified based on three preset qualification standards. Only slurries that are qualified in all three aspects can be used for the preparation of positive electrode sheets. S3: Add qualified solid electrolyte slurry to the positive electrode slurry in proportion, and then homogenize, coat and dry to make a positive electrode sheet; S4: Test the moisture content of the positive electrode sheet and confirm that it meets the requirements.

[0010] Preferably, the specific method for testing the total moisture content of the slurry in step S1 is as follows: Take 0.2~0.3g of solid electrolyte slurry at an environment with a dew point temperature ≤-50℃. When the Karl Fischer moisture analyzer drift value is <10μg / min, inject the slurry into an aldehyde-ketone Karl Fischer reagent through a needle for testing. The stirring speed is 60%.

[0011] Preferably, the specific method for testing the moisture content of the supernatant after centrifugation in step S1 is as follows: Take 30 mL of solid electrolyte slurry at a dew point temperature ≤ -50℃, centrifuge at 10000 rpm for 30 min, take 0.2~0.3 g of supernatant, and test when the Karl Fischer moisture analyzer drift value is <10 μg / min.

[0012] Preferably, the specific method for testing the moisture content of the lower layer of wet powder after centrifugation in step S1 is as follows: a. Take 30 mL of solid electrolyte slurry, centrifuge at 10000 rpm for 30 min, and seal 3 g of the lower layer of wet powder. b. Transfer the wet powder to an inert gas glove box with a water content of <0.1ppm, heat at 110℃ for 30min to remove the solvent, grind into fine powder and continue heating for 20min; c. Take 0.2g of the treated powder, and when the Karl Fischer moisture analyzer drift value is <10μg / min, place it in a heating furnace and heat it at 180℃ for 600s. Use 50mL / min of high-purity inert gas to purge water vapor into the Karl Fischer reagent for testing.

[0013] Preferably, the three qualification criteria in step S2 are: The total moisture content of the slurry is ≤200ppm, the moisture content of the supernatant after centrifugation is ≤100ppm, and the moisture content of the lower wet powder after centrifugation is ≤250ppm.

[0014] Preferably, the solid electrolyte added in step S3 is 1%-5% of the total mass of the effective components in the positive electrode slurry, and the effective components of the positive electrode slurry include the positive electrode main material, binder, conductive agent and solid electrolyte.

[0015] Preferably, the solid electrolyte slurry has a D50 particle size of 0.1-1 μm, a solid content of 10-50 wt.%, and is a non-aqueous organic solvent.

[0016] Preferably, the solid electrolyte is selected from one or more of perovskite-type, garnet-type, NASICON-type, LiSICON-type solid electrolytes, titanium dioxide, aluminum oxide, and phosphate solid electrolytes.

[0017] Preferably, the specific method for testing the moisture content of the positive electrode in step S4 is as follows: Take 1g of electrode sample, weigh it accurately, and place it in a heating furnace. Heat it at 180℃ for 600s, purge it with inert gas at 50mL / min, and stir it with Karl Fischer reagent at 60%. The moisture content of the positive electrode is ≤180ppm.

[0018] On the other hand, a lithium-ion battery is provided, comprising a positive electrode sheet prepared by the preparation method described above.

[0019] Finally, a method for electrolyte moisture control in the preparation of positive electrode sheets to significantly improve their yield is provided, comprising the following steps: Three independent moisture tests were performed on the solid electrolyte slurry: total moisture content of the slurry, moisture content of the supernatant after centrifugation, and moisture content of the lower wet powder after centrifugation. Whether a solid electrolyte slurry is qualified is determined based on whether it meets the three preset qualification standards simultaneously.

[0020] Preferably, the specific method for testing the total moisture content of the slurry in step S1 is as follows: Take 0.2~0.3g of solid electrolyte slurry at an environment with a dew point temperature ≤-50℃. When the Karl Fischer moisture analyzer drift value is <10μg / min, inject the slurry into an aldehyde-ketone Karl Fischer reagent through a needle for testing. The stirring speed is 60%.

[0021] Preferably, the specific method for testing the moisture content of the supernatant after centrifugation in step S1 is as follows: Take 30 mL of solid electrolyte slurry at a dew point temperature ≤ -50℃, centrifuge at 10000 rpm for 30 min, take 0.2~0.3 g of supernatant, and test when the Karl Fischer moisture analyzer drift value is <10 μg / min.

[0022] Preferably, the specific method for testing the moisture content of the lower layer of wet powder after centrifugation in step S1 is as follows: a. Take 30 mL of solid electrolyte slurry, centrifuge at 10000 rpm for 30 min, and seal 3 g of the lower layer of wet powder. b. Transfer the wet powder to an inert gas glove box with a water content of <0.1ppm, heat at 110℃ for 30min to remove the solvent, grind into fine powder and continue heating for 20min; c. Take 0.2g of the treated powder, and when the Karl Fischer moisture analyzer drift value is <10μg / min, place it in a heating furnace and heat it at 180℃ for 600s. Use 50mL / min of high-purity inert gas to purge water vapor into the Karl Fischer reagent for testing.

[0023] Preferably, the three qualification criteria in step S2 are: The total moisture content of the slurry is ≤200ppm, the moisture content of the supernatant after centrifugation is ≤100ppm, and the moisture content of the lower wet powder after centrifugation is ≤250ppm.

[0024] When the slurry to be tested meets all three of the above qualification standards, it can meet the requirements for the moisture content of the subsequent electrode sheets, thus greatly improving the qualification rate of the electrode sheets.

[0025] The beneficial effects of the technical solutions provided in the embodiments of the present invention include at least the following: 1. Established the industry's first three-dimensional moisture control system For the first time, a multi-dimensional control method of "total moisture in slurry + moisture in centrifuged supernatant + moisture in the lower layer of wet powder after centrifugation" was proposed, which comprehensively covers free water and adsorbed water in solid electrolyte slurry, solves the problem of insufficient traditional single control dimension, and realizes a comprehensive assessment of the moisture state of slurry.

[0026] 2. The underlying cause of excessive moisture content in the electrode sheets was revealed. Through comparative experiments, the core principle that "the moisture content of solid electrolyte wet powder is the key factor affecting the moisture content of electrode sheets" was clarified for the first time, correcting the long-standing misconception in the industry that "controlling the total moisture content of the slurry is sufficient" and providing a scientific theoretical basis for moisture control.

[0027] 3. Fills the industry gap in wet powder moisture testing. A standardized method for testing the moisture content of wet powder solid electrolyte slurry has been developed, including a complete process such as centrifugation, solvent removal, and high-temperature vaporization testing. This method can accurately quantify the adsorbed water content on the surface of nanoparticles, and the test results have good repeatability and high accuracy.

[0028] 4. Enables early prediction and risk mitigation of electrode moisture content. By moving the moisture control point from after electrode preparation to before slurry use, and by testing three indicators, it is possible to predict with 100% accuracy whether the moisture content of the electrode will exceed the standard, fundamentally avoiding the risk of scrapping the entire batch of electrodes.

[0029] 5. Significantly reduce production costs and improve production efficiency. The moisture content of the electrode sheets has been reduced from 15%-20% using traditional methods to 0%, reducing raw material loss by more than 80%. At the same time, it avoids the time and labor costs of rework and scrap disposal, and increases production efficiency by more than 30%.

[0030] 6. Improve battery performance and safety By strictly controlling the moisture content of the electrode sheets, the side reactions inside the battery are effectively reduced, improving the battery's capacity retention rate (capacity retention rate improved by 5%-8% after 1000 cycles), rate performance, and cycle life. At the same time, it reduces safety hazards such as gas expansion and thermal runaway caused by excessive moisture. Attached Figure Description

[0031] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0032] Figure 1 This is a schematic diagram of water distribution in a solid electrolyte slurry; Figure 2 This is a schematic diagram of a preparation process provided in an embodiment of the present invention. Detailed Implementation

[0033] The technical solution of the present invention will now be described with reference to the accompanying drawings.

[0034] In embodiments of the present invention, words such as "exemplarily," "for example," etc., are used to indicate that something is an example, illustration, or description. Any embodiment or design described as "exemplary" in the present invention should not be construed as being more preferred or advantageous than other embodiments or designs. Specifically, the use of the word "exemplary" is intended to present the concept in a concrete manner. Furthermore, in embodiments of the present invention, the meaning expressed by "and / or" can be both, or either one.

[0035] In the embodiments of this invention, the terms "image" and "picture" may sometimes be used interchangeably. It should be noted that, without emphasizing the distinction between them, they convey the same meaning. Similarly, the terms "of," "corresponding (relevant)," and "corresponding" may sometimes be used interchangeably. It should be noted that, without emphasizing the distinction between them, they convey the same meaning.

[0036] In this embodiment of the invention, sometimes a subscript such as W1 may be mistakenly written as a non-subscript form such as W1. When the difference is not emphasized, the meaning they express is the same.

[0037] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.

[0038] This solution can be applied to battery manufacturing processes using non-aqueous solid electrolytes or other forms such as inorganic functional materials. This application primarily uses solid electrolytes as an example; other products that can be improved based on the technical principles of this application are still within the scope of extension and protection of this application.

[0039] I. Purpose of the Invention This invention addresses the aforementioned technical problems by providing an effective method for controlling the moisture content of mixed solid electrolyte electrodes, specifically solving the following technical issues: ① This addresses the industry pain point of introducing additional moisture into the electrode due to the mixing of solid electrolyte slurry, which leads to excessive moisture content in the electrode sheet; ② Correct the misconception in the existing technology that "controlling the overall moisture content of the slurry is sufficient to ensure the moisture content of the electrode sheet is up to standard" and clarify that the moisture content of the wet powder is the key factor affecting the moisture content of the electrode sheet; ③ Filling a gap in the industry, it provides a standardized method for testing the moisture content of wet powder solid electrolyte slurry.

[0040] This invention establishes a three-dimensional control system of "total moisture in slurry - moisture in centrifuged supernatant - moisture in the lower layer of wet powder after centrifugation", which advances the moisture control point from after the electrode preparation is completed to before the slurry is used, so as to realize the early prediction and risk control of electrode moisture, and fundamentally reduce the risk of excessive moisture in the mixed solid electrolyte electrode.

[0041] II. Content 1. Basic components of solid electrolyte slurry Solid electrolyte slurries typically consist of oxide solid electrolyte powder, non-aqueous organic solvents, and dispersants, with the dispersant content being less than 5% of the total mass of inorganic particles.

[0042] Solid electrolyte: selected from one or more of perovskite type, garnet type, sodium superion conductor (NASICON type), lithium superion conductor (LiSICON type) and phosphate solid electrolyte, and may preferably be phosphate solid electrolyte or inorganic functional materials such as alumina, titanium oxide, and silicon oxide; Particle size parameter: D50 is 0.1~1μm; Solid content: 10~50 wt.% The solvent is a non-aqueous organic solvent; First, the moisture content of the solid electrolyte slurry, the moisture content of the centrifuged supernatant, and the moisture content of the lower wet powder are tested. After all tests are qualified, the slurry is added to the electrode slurry to make the electrode sheet. After normal sheet making, the moisture content of the electrode sheet is tested and it meets the requirements of the electrode sheet moisture content.

[0043] 2. A method for preparing a positive electrode based on electrolyte moisture control The core of this method is to comprehensively evaluate the moisture state of solid electrolyte slurry through three independent moisture tests. Only slurry that meets all three indicators can be used for cathode preparation.

[0044] like Figure 2 As shown, the specific steps are as follows: Step 1: Standardized testing of three moisture indicators ① Total moisture content test of solid electrolyte slurry a. Sample collection: Accurately weigh 0.2~0.3g of solid electrolyte slurry in a dry environment with a dew point temperature ≤-50℃; b. Instrument preparation: Adjust the Karl Fischer moisture analyzer to a stable state, ensuring that the drift value is <10μg / min; c. Test Procedure: Using a syringe, slowly inject the slurry into the aldehyde / ketone Karl Fischer reagent through the needle. Set the stirring speed to 60%. Record the data after the test results stabilize. The reagents used are aldehyde / ketone Karl Fischer reagent (anolyte) and catholyte.

[0045] ② Moisture content test of the supernatant after centrifugation a. Sample preparation: Under a dry environment with a dew point temperature ≤ -50℃, take 30mL of solid electrolyte slurry and place it in a centrifuge tube. Centrifuge at 10000rpm for 30min. After standing, carefully aspirate the supernatant. b. Test operation: Accurately weigh 0.2~0.3 g of the supernatant, conduct the test when the drift value of the Karl Fischer moisture meter is <10 μg / min, add the supernatant to the Karl Fischer reagent to test the water content, and the operation is the same as that for testing the total moisture of the slurry.

[0046] ③ Testing of moisture content of lower-layer wet powder after centrifugation a. Slurry centrifugation, with steps and parameters the same as those in the preparation process of supernatant samples; b. Take 3 g of the lower-layer wet powder after centrifugation, seal it, transfer it to a glove box filled with inert gas (nitrogen, argon) with water content <0.1 ppm, heat the wet powder to evaporate excess solvent, bake at 110°C for 30 min (the same as the drying temperature of the positive electrode sheet), grind the dried agglomerated powder into fine powder with a mortar, continue baking on a heating plate for 20 min, take 0.3 g of the sample and seal it.

[0047] c. When the drift value of the moisture meter is <10 μg / min, take about 0.2 g of the powder sample, accurately weigh the mass, put it into a heating furnace, heat at 180°C for 600 s, use high-purity inert gas to purge the vaporized water vapor into the Karl Fischer reagent to conduct the water content test, with a gas flow rate of 50 mL / min and a stirring speed of the Karl Fischer reagent of 60%.

[0048] Step 2: Qualification criteria for moisture Verified by a large number of experiments, the qualification thresholds for the following three moisture indicators are established (Table 1), and whether the moisture of the solid electrolyte slurry is qualified is determined according to the standard. Only the slurry that meets the requirements of all three indicators at the same time can be judged as qualified:

[0049] Table 1 Qualification standards for moisture of solid electrolyte slurry Note: Among the three indicators, the moisture of the lower-layer wet powder after centrifugation has the greatest influence on the moisture of the electrode sheet, which is the core control item.

[0050] Step 3: Preparation and final verification of positive electrode sheet Add the judged-qualified solid electrolyte slurry to the positive electrode slurry in a preset proportion, and prepare the positive electrode sheet by a conventional wet homogenization process: Components of the positive electrode sheet: composed of main positive electrode materials (lithium iron phosphate, ternary lithium, etc.), conductive agents (CNTs, SP, etc.), binders (PVDF, etc.); Preparation process: homogenization→coating→drying→rolling→slitting; Moisture test of electrode sheet: take about 1 g of electrode sheet sample, accurately weigh it and put it into a heating furnace, the test parameters are heating at 180°C for 600 s, purging with inert gas at 50 mL / min, and the stirring speed of Karl Fischer reagent is 60%; Electrode moisture content standard: ≤180ppm.

[0051] To verify the effectiveness of the method of the present invention, a comparative experiment was conducted using two batches of solid electrolyte slurries with different moisture states. The specific implementation process is as follows: Example

[0052] To compare the effects of solid electrolytes with acceptable and unacceptable moisture content on electrode moisture, three batches of solid electrolyte slurries with different moisture contents were added to the positive electrode in proportion to form positive electrode sheets. The effects of solid electrolyte slurry moisture content and moisture content of the wet powder after centrifugation on electrode moisture content were compared, thereby enabling early identification of the risk of slurry moisture content affecting electrode moisture content.

[0053] 1. Moisture content test of solid electrolyte A batch of newly prepared solid electrolyte slurry N001 with qualified moisture content was selected. The specifications were: particle size D50=200nm, solid content 20wt.% oil-based slurry, main component LATP, solvent NMP. The results of testing the moisture content of the slurry, the supernatant of centrifugation, and the wet powder of the lower layer of centrifugation are shown in Table 2 below. Solid electrolyte slurry was stored in a dry room (dew point -40℃) for 60 days, resulting in slurry N002 with high moisture content. The moisture content of the slurry and the supernatant after centrifugation were within acceptable limits, but the moisture content of the wet powder exceeded the standard. The test results of various moisture contents are shown in Table 2 below. Solid electrolyte slurry was stored in a non-dry room environment for 4 hours to obtain slurry N003 after absorbing water from the air. The moisture content of the slurry, the moisture content of the supernatant after centrifugation, and the moisture content of the wet powder in the lower layer after centrifugation all exceeded the standard. The test results of each moisture content are shown in Table 2 below.

[0054] Specifically as follows: (1) Slurry moisture test With the ambient dew point at -58.6℃, adjust the moisture meter settings and set the stirring speed to 60%. Once the drift value is <10 ug / min, accurately weigh three parallel test samples of solid electrolyte slurry (0.205g / 0.208g / 0.202g). Use a syringe to inject the slurry into the anolyte. After the test results stabilize, obtain the moisture test results from the equipment and record the data. See Table 2 below for specific data.

[0055] Note: Only one sample is tested at a time, and the equipment status needs to be readjusted after each test.

[0056] (2) Moisture content test of centrifuged supernatant Weigh 30g of solid electrolyte slurry using a 50mL centrifuge tube, centrifuge at 10000rpm for 30min, remove the supernatant, and then accurately weigh three supernatant samples (0.201g, 0.205g, and 0.207g) using a syringe. Inject these samples into the anolyte for testing. After stabilization, obtain the moisture test results and record the data. See the table below for specific data.

[0057] (3) Moisture content test of the lower layer of wet powder after centrifugation Weigh 30g of solid electrolyte slurry using a 50mL centrifuge tube, centrifuge at 10000rpm for 30min, retain the lower layer of wet powder, seal and transfer to a glove box, moisture content <0.1ppm, spread the wet powder on an aluminum tray, heat the powder on the aluminum tray using a heating stage, hold at 110℃ for 30min, then grind the clumps into fine powder using a mortar and pestle, continue heating for 20min, take a sample of about 0.3g, accurately weigh three powder samples of 0.201g / 0.203g / 0.205g, place them in the heating furnace, and start testing the moisture content after the equipment drift value is <10ug / min, heat at 180℃ for 600s, and after the test stabilizes, obtain the moisture test results and record the data. See Table 2 below for specific data.

[0058] According to the three test methods of this invention, the moisture content of the three slurries N001-N003 was tested respectively, and the average results are shown in Table 2 below:

[0059] Table 2 Comparison of Moisture Test Results for Solid Electrolyte Slurry The three-dimensional control system of this invention can accurately identify hidden risks that cannot be detected by methods that only control the total moisture content of slurry. The total moisture content of slurry N002 meets the slurry standard, but the moisture content of the wet powder is severely excessive (448.19 ppm > 250 ppm). This method can preemptively determine it as unqualified, avoiding the scrapping of subsequent electrode sheets; while controlling only the total moisture content of the slurry may misjudge it as qualified, leading to the final electrode sheet having excessive moisture content. For slurry N003, because the slurry is exposed to a non-drying environment, it absorbs moisture from the environment and exceeds the standard. The particles in the slurry, due to their small particle size and large specific surface area, easily absorb moisture from the air and solvent, resulting in excessive moisture content in the lower layer of wet powder after centrifugation. The total moisture content of slurry N003, the moisture content of the supernatant after centrifugation, and the moisture content of the lower layer of wet powder after centrifugation all exceed the standard. Adding it to the electrode sheet may lead to excessive moisture content in the electrode sheet.

[0060] 2. Preparation and Moisture Testing of Positive Electrode Sheets Using a wet homogenization process, the NCM cathode material, CNTs, SP, PVDF binder, and NMP were homogenized using a Ross mixer. 3% of solid electrolyte slurries N001, N002, and N003 were added to the three electrode slurry samples respectively (CNTs:PVDF:LATP = 94.75:1:0.25:1:3). Homogenization and sheet preparation were then performed, with a coating surface density of 210 g / m³. 2 After coating, the solvent is dried. The electrode sheets are baked and then tested for moisture content. Approximately 1g of electrode sheet sample is taken, accurately weighed, and placed in the heating furnace of a moisture analyzer for testing at 180℃ for 600s. The test results are recorded and are shown in Table 3 below.

[0061] Table 3 Comparison of moisture test results for positive electrode sheets The experimental results show that the electrode prepared using N001 slurry, which meets all three indicators, has a moisture content (126.7 ppm) far below the acceptable standard; the electrode prepared using N002 slurry, which only has excessive moisture content in the lower layer of wet powder after centrifugation (220.3 ppm), also has excessive moisture content; the electrode prepared using N003 slurry, which has excessive moisture content in total slurry, supernatant after centrifugation, and lower layer of wet powder after centrifugation (267.9 ppm), has a relatively greater excess of moisture content. This fully demonstrates the accuracy and effectiveness of the method of the present invention.

[0062] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for preparing a positive electrode based on electrolyte moisture control, characterized in that, Includes the following steps: S1: Three independent moisture tests were performed on the non-aqueous solid electrolyte slurry: total moisture content of the slurry, moisture content of the supernatant after centrifugation, and moisture content of the lower wet powder after centrifugation. S2: Determine whether the solid electrolyte slurry is qualified based on three preset qualification standards. Only slurries that are qualified in all three aspects can be used for the preparation of positive electrode sheets. S3: Add qualified solid electrolyte slurry to the positive electrode slurry in proportion, and then homogenize, coat and dry to make a positive electrode sheet; S4: Test the moisture content of the positive electrode sheet to confirm that it meets the requirements.

2. The preparation method according to claim 1, characterized in that, The specific method for testing the total moisture content of the slurry in step S1 is as follows: Solid electrolyte slurry samples were taken in a dry room environment with a dew point temperature ≤ -50℃. When the Karl Fischer moisture analyzer drift value was <10μg / min, the mass of the slurry sample was accurately weighed and injected into an aldehyde-ketone Karl Fischer reagent for testing. After the test results stabilized, the moisture value was read by the device.

3. The preparation method according to claim 1, characterized in that, The specific method for testing the moisture content of the supernatant after centrifugation in step S1 is as follows: Solid electrolyte slurry was taken at a dew point temperature ≤ -50℃, and a certain amount of supernatant was collected by centrifugation. When the drift value of the Karl Fischer moisture analyzer was <10μg / min, the centrifuged supernatant was injected into the Karl Fischer reagent for testing, and the moisture test results were read by the equipment.

4. The preparation method according to claim 1, characterized in that, The specific method for testing the moisture content of the lower layer of wet powder after centrifugation in step S1 is as follows: a. Centrifuge the solid electrolyte slurry and seal a certain amount of the lower wet powder layer. b. Transfer the wet powder to an inert gas glove box with a moisture content of <0.1ppm, heat to remove the solvent, grind into fine powder, and continue heating for a period of time; c. Take a certain amount of the treated powder, accurately weigh it when the Karl Fischer moisture analyzer drift value is <10μg / min, put it into a heating furnace for heating, use high-purity inert gas to purge water vapor into the Karl Fischer reagent for testing, and read the moisture test results from the equipment.

5. The preparation method according to claim 1, characterized in that, The three qualification criteria mentioned in step S2 are: The total moisture content of the slurry is ≤200ppm, the moisture content of the supernatant after centrifugation is ≤100ppm, and the moisture content of the lower wet powder after centrifugation is ≤250ppm.

6. The preparation method according to claim 1, characterized in that, The solid electrolyte added in step S3 is 1%-5% of the total mass of the effective components in the positive electrode slurry.

7. The preparation method according to claim 1, characterized in that, The solid electrolyte slurry has a D50 particle size of 0.1-1 μm, a solid content of 10-50 wt.%, and is a non-aqueous organic solvent.

8. The preparation method according to claim 1, characterized in that, The solid electrolyte is selected from one or more of the following: perovskite type, garnet type, NASICON type, LiSICON type solid electrolyte, titanium dioxide, aluminum oxide, and phosphate solid electrolyte.

9. The preparation method according to claim 1, characterized in that, The specific method for testing the moisture content of the positive electrode in step S4 is as follows: Take an electrode sample, weigh it accurately, place it in a heating furnace, heat it, and use an inert gas to purge the volatile water vapor into the Karl Fischer reagent. After the test is completed, read the electrode moisture test result from the equipment; the qualified standard for positive electrode moisture is ≤180ppm.

10. A lithium-ion battery, characterized in that, It includes a positive electrode sheet prepared by the preparation method according to any one of claims 1-9.

11. A method for controlling electrolyte moisture, characterized in that, Includes the following steps: Three independent moisture tests were performed on the solid electrolyte slurry: total moisture content of the slurry, moisture content of the supernatant after centrifugation, and moisture content of the lower wet powder after centrifugation. Whether a solid electrolyte slurry is qualified is determined based on whether it meets the three preset qualification standards simultaneously.